Donkey-Hide Gelatin Peptide-Iron Complexes: Structural Characterization, Enhanced Iron Solubility Under Simulated Digestion, and Dual Iron Chelation-Antioxidant Functions - Lili Yang; Chenyan Lv; Xingfeng Guo; Rong Liang (Foods)
Iron deficiency is a global health issue, making the development of novel iron supplements to enhance iron absorption critically important. In this study, low molecular weight donkey-hide gelatin peptides (LMW DHGP) were enzymatically hydrolyzed from donkey-hide gelatin. Experimental results demonstrated that the iron chelating capacity of LMW DHGP reached 249.98 μg/mg. Key amino acids (Asn, Gly, Cys, Lys) may participate in chelation. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis showed rough, porous amorphous structures of LMW DHGP-iron complexes. The results of circular dichroism spectroscopy (CD) indicated that the self-assembly of LMW DHGP-iron complexes appears to be primarily mediated by peptide α-helical structural conformations. Fourier transform infrared (FTIR) spectroscopy further indicated that the interaction between LWM DHGP and Fe2+ likely occurs through carboxyl and amino functional groups. In vitro digestion stability studies demonstrated that LMW DHGP-iron complexes exhibited superior iron ion solubility compared to FeSO4 in simulated gastrointestinal conditions. PGPAG-iron complexes exhibited the highest antioxidant activity, with scavenging rates of 71.64% (DPPH radical) and 88.79% (ABTS radical). These findings collectively suggest that LMW DHGP-iron complexes possess significant potential as a novel iron supplement in food applications, which provides valuable theoretical insights for the development of innovative iron supplementation strategies.